Long‐term outcomes of intestinal transplantation from donors aged under 1 year. (23rd February 2022) - Chang, Yu‐Tang; Soltys, Kyle; Khanna, Ajai; Bond, Geoffrey J.; Ganoza, Armando; Rudolph, Jeffrey A.; Sindhi, Rakesh; Mazariegos, George V.
Abstract: Background: The aim of the study was to analyze the long‐term outcomes of transplants utilizing ITx donors <1 year and to compare these results with older donors. Methods: Between January 2007 and December 2019, the primary ITx donors in the Children's Hospital of Pittsburgh of UPMC were retrospectively reviewed. Short‐ and long‐term outcomes of recipients receiving a deceased donor organ from donors <1 year were compared with those found in all other recipients. Results: During the study period, there were 89 primary ITx donors, using 30 donors (33.7%) aged <1 year. The mean age of their recipients was 1.6 ± 0.7 (0.7–3.2) years. The 30 graft types were isolated intestine ( n = 3, 10.0%), liver bowel ( n = 20, 66.7%), and multivisceral ( n = 7, 23.3%). Technical complications occurred in 12 (40.0%) recipients. Candidates transplanted with intestine allografts from donors <1 year of age had shorter wait times ( p < .001), more liver‐inclusive grafts ( p < .001), and less donor‐specific antibodies (DSA) ( p = .014). During follow‐up, the recipients had less graft loss ( p = .018), and more remained alive with graft in place ( p = .011). Among children transplanted with such donors, 3‐year and graft survival rates were 86.7% and 82.9% compared to 62.8% and 49.9% in the cohort of donors >1 year ( p = .032 and .011). Conclusions: Donor age <1 year was associated with improved graft survival. Optimal utilization of this population for toddler candidates would increase intestine availability, reduce time to transplantation, and potentially improve long‐term outcome.